ALIRAN MUTAZILAH DALAM LINTASAN SEJARAH PEMIKIRAN ISLAM - Mawardy Hatta (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
One school of Kalam/Islamic theology that once flourished in antiquity was Mu'tazila flow. Flow pattern known as rational and liberal thought that was growing and evolving so rapidly and peaked in the Abbasid era in particular Khalifah Al- Ma'mun because of the support and protection of the khalifah. But then, the glory and the gold period did not last long, it eventually flew into decline. It was caused by a variety of factors, most importantly; they had done violence coercion and even torture of a number of scholars in the event of al - mihnah when imposing the concept of